Lagaan : Once upon a time in India - Gowariker, Ashutosh (Columbia : Aamir Khan Production, 2002)
Queen Victoria's India. the year is 1893. Champaner...a small farming village in Central India. On the outskirts of the village stands a British cantonment, commanded by Captain Russell (Paul Blackthorne) - an arrogant and capricious man, who wields the power of life and death over the village under his jurisdiction. Lagaan - a story of a battle without bloodshed. Fought by a group of unlikely heroes led by Bhuwan (Aamir Khan), an enigmatic young farmer with courage born of conviction - and a dream in his heart. Helped by Elizabeth (Rachel Shelley), an English rose, who came to India and lost her heart, and Bhuwan's pillar of strength, Gauri (Gracy Singh), the young and perky village girl, who dreams only of a home with the man she loves. A story of extraordinary circumstances thrust upon ordinary people. Adversity faces with fortitude and injustice with dignity. Faith and courage come face to face with arrogance and ruthlessness... and the human spirit triumph.